Anxiety and depression in patients with advanced macular degeneration: current perspectives - Cimarolli, Verena R (Clin Ophthalmol, 2015)
Age-related macular degeneration (AMD) – despite advances in prevention and medical treatment options – remains prevalent among older adults, often resulting in functional losses that negatively affect the mental health of older adults. In particular, the prevalence of both anxiety and depression in patients with AMD is high. Along with medical treatment options, low vision rehabilitation and AMD-specific behavioral and self-management programs have been developed and have demonstrated effectiveness in improving the mental health of AMD patients. This article reviews the prevalence of anxiety and depression in patients with advanced AMD, discusses potential mechanisms accounting for the development of depression and anxiety in AMD patients, presents the state-of the-art of available interventions for addressing anxiety and depression in AMD patients, and delineates recommendations for eye care professionals regarding how to screen for these two prevalent mental health problems and how to facilitate appropriate treatment for patients with AMD.